2017
DOI: 10.1590/1678-457x.27716
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization, texture and consumer acceptability of yogurts supplemented with quinoa flour

Abstract: Quinoa can be used as a functional ingredient in food formulations. The aim of this study was to evaluate the effects on proximate composition, stability during storage, texture and consumer acceptability of yogurts supplemented with quinoa flour at 1, 3 and 5 g 100 mL -1. A product without supplementation was used as control. Products were assessed for moisture, carbohydrates, proteins, fats, total dietary fibre (TDF), ashes and minerals. The pH, acidity and syneresis of yogurts were measured after 1, 7, 14 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 19 publications
4
22
0
6
Order By: Relevance
“…As a result of the research, they found that the addition of quinoa flour caused a decrease in pH values. Curti, Vidal, Curti, and Ramón (2017) found that when adding different amounts of quinoa (1%, 3%, and 5%) to yogurts, the pH of yogurts decreased due to storage, and that the yogurt affected the gel structure, and that it was important to affect consumers.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the research, they found that the addition of quinoa flour caused a decrease in pH values. Curti, Vidal, Curti, and Ramón (2017) found that when adding different amounts of quinoa (1%, 3%, and 5%) to yogurts, the pH of yogurts decreased due to storage, and that the yogurt affected the gel structure, and that it was important to affect consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, quinoa starch grains are small in size and highly stable, making this starch applicable as substitute for chemically modified starches (Sharma et al ). Recently, Codină et al () and Curti et al () successfully applied quinoa flour in cow's milk yoghurt, resulting in high viscosity and nutritional value. However, it negatively affected the texture and the overall acceptability when added at more than 1 g/100 mL in a product.…”
Section: Introductionmentioning
confidence: 99%
“…Curti et al 45 and Hasani et al 4 added, respectively, quinoa flour at concentrations of 1.0%, 3.0% and 5.0% and barley bran at concentrations of 0.300%, 0.600%, 0.900% and 1.20% in yogurts and verified that higher cereal concentrations can affect texture as well as influence flavor and aroma, and thus contribute to product rejection. In general, the addition of cereals in yogurts causes a sandy texture, influenced by the type of cereal and its concentration 3,46 .…”
Section: Discussionmentioning
confidence: 95%
“…According to Curti et al 45 , overall acceptability is a complex term that comprises the combination of different sensory perceptions. In this context, the rejection by the consumer of any of the sensorial characteristics can negatively influence the general perception of the yogurt.…”
Section: Discussionmentioning
confidence: 99%